Prevalence, Risk Factors and Major Bacterial Causes of Bovine Mastitis in Smallholder Dairy Farms in and around Sinana District, Bale Zone, South Eastern Ethiopia (Global Journal of Science Frontier Research, 2018)
A cross-sectional study was conducted from November 2013 to May 2014 on lactating dairy cows to determine the overall prevalence of bovine mastitis, identify associated risk factors and isolate the predominant bacterial agents involved in causing mastitis in and around Sinana district. A total of 384 lactating cows were examined for mastitis using clinical examination and California Mastitis Test (CMT). Bacteriological isolation techniques were also undertaken to recover the causative bacterial pathogens. Prevalence of mastitis at cow level was 36.72%, out of which 4.95% and 31.77% were clinical and subclinical cases, respectively. The quarter level prevalence was 26.43%; from this, the clinical and subclinical forms were 2.28% and 24.15%, respectively. Out of total examined teats, 1.30% was blind. About 356 bacterial isolates identified from mastitic milk samples. The isolates based on their relative frequency of occurrence were: Staphylococcus aureus (33.99%), Streptococcus agalactiae (24.44%), Staphylococcus epidermidis (10.96%), Coagulase-Negative Staphylococci (CNS) (7.58%), Escherichia coli (6.46%), Streptococcus dysgalactiae (6.18%), Corynebacterium bovis (5.34%), Klebsiella pneumonia (2.81%) and Bacillus cereus (2.23%).
Keywords: bacterial isolates; bovine mastitis; lactating cow; prevalence; risk factors; sinana